The Use of Cyberbullying Mobile Application to Increase Perceived Knowledge of Cyberbullying Among Adolescents - Orawit Thinnukool (2018)
© 2018 World Scientific Publishing Company The aim of this study was to develop a research-based mobile application to increase perceived knowledge of Thai adolescents on cyberbullying. The proposed mobile application is called Cyberbullying Mobile Application (CBMA) which is the first research-based CBMA developed in Thailand. The research focused on the lack of adolescent perceived knowledge on the above, at the undergraduate level. Two hundred and fifty-three samples were surveyed from high schools and universities. After releasing the CBMA for real use to the same group of users as the samples, the study found that users appreciated it and had confidence in the application; while in some cases, users claimed they would use it in their lives. The CBAM and questionnaire outcomes were analyzed by using independent sample (Formula presented.)-test analysis on (Formula presented.) program to test hypothesis. Therefore, the CBMA is an appropriate tool recommended for adolescents to educate themselves to handle and be aware of cyberbullying.